Prevalence of Selected Immune Evasion Genes and Clonal Diversity in Methicillin-Susceptible Staphylococcus aureus Isolated from Nasal Carriers and Outpatients with Cut Wound Infections - Gabriela Jura; Helena Masiuk; Agata Pruss; Mateusz Kurzawski; Monika Sienkiewicz; Iwona Wojciechowska-Koszko; Paweł Kwiatkowski (MDPI AG, 2024)
Staphylococcus aureus, being one of the most common human pathogens, is responsible for infections in both hospital and community settings. Its virulence is attributed to its ability to evade the immune system by producing immune evasion (IE) proteins. The aim of this study was to detect the frequency of selected IE genes (spin, sbi, sea, sak, chp, scin, sep, ecb), belonging to the immune evasion cluster (IEC), and IEC types in 86 methicillin-susceptible S. aureus (MSSA) strains isolated from unrelated outpatients. In order to determine the diversity of analyzed strains, the phylogenetic relatedness was also determined. All strains were examined for the presence of IE genes using polymerase chain reaction assay. To analyze the clonal relatedness of S. aureus, pulsed-field gel electrophoresis (PFGE) was performed. All analyzed strains harbored the scn gene, followed by sbi (95.4%), ecb (91.7%), spin (89.5%), sak (83.7%), chp (67.4%), sep (67.4%) and sea (5.8%). Seventy-three (84.9%) S. aureus strains were classified into IEC types, of which, IEC type F was most commonly observed. IEC type A was not detected. PFGE results showed no association between clonal relatedness and the presence of IE genes/IEC types. In conclusion, the abundant and so diverse repertoire of genes determining invasion in analyzed strains may prove the fact that these strains are highly advanced and adapted to evade the host immune response.